Search engine optimization all-in-one for dummies - Clay, Bruce (--For dummies., 2009)
"If you have a business, you want your Web site to show up quickly when people search for what you're selling. Search Engine Optimization All-in-One For Dummies has the whole story on how to build a site that works, position and promote it, track and understand your search results, and use keywords effectively. Ten handy minibooks cover how search engines work, keyword strategy, competitive positioning, SEO Web design, content creation, linking, optimizing the foundations, analyzing results, international SEO, and search marketing. You'll even learn some geeky things like HTML, JavaScript, and CSS, or how to match metatags and keywords to page content"--Resource description page.